Metabólitos secundários obtidos através do estudo das raízes de Psychotria prunifolia (Kunth) Steyerm (Rubiaceae), transformações e ensaios biológicos de seu extrato - RIBEIRO, Laryssa Campos (2010)
Psychotria prunifolia is an endemic shrub from the Goias cerrado that belongs to the Rubiaceae family and to the Psychotrieae tribe. Extracts and fractions from Psychotria genera species are known for its cytotoxic potentials, and a wide range of studies have reported anticancer activity as well as the presence of nonmonoterpenic indole alkaloids and iridoids. Alkaloids are also used as chemotaxonomic indicators by means of classification of the species from such genera and the Psychotria and Heteropsychotria subgenera. This study focuses on the phytochemical assay of the P. prunifolia roots, the chemical transformations of two of the metabolites obtained, and the evaluation of antioxidant and molluscicidal crude roots, stems and leaves extracts activity. Column chromatography fractioning of crude roots extract and submission to successive layer preparative chromatography led to the isolation of five compounds: sitosterol (LCPP-1), a benzidenone derivative (LCPP-2) not yet described for this family, and three β-carboline alkaloids (LCPP-3, LCPP-4 and LCPP-5). Alkaloid LCPP-4 is unpublished and the others have already been isolated from the leaves of this species. The acid-base fractionation allowed the isolation of strictosamide (LCPP-6), a well known alkaloid isolated from the leaves of this species and other species of this genus. Chemical transformation of the alkaloid LCPP-3 to LCPP-4 have been observed through their 1H, 13C, HSQC, and HMBC NMR-spectra. Some suggestions for these transformations were proposed. Crude extract from roots, branches and leaves were evaluated using the DPPH radical scavenging method, and a 50% loss in absorbance was observed in 145, 162.4, and 231.6 ppm concentrations, respectively. The molluscicidal assay with the crude roots extract of showed no activity.